(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The aim of this comparative article is to show the differences between the visitors' purposes and habits in two national parks: Gauja National Park (GNP) in Latvia and Kasu Bramhananda Reddy National Park (KBR) in Hyderabad, Telangana in India. As well as that, the article aims at highlighting differences in the functional use of the national parks and their locations in the urban and rural context. The study has used the secondary data analysis, such as the analysis and overview of the literature, previously conducted studies and information sources, visitors’ surveys in the national parks, and the exploration of the park areas for the evaluation of tourism infrastructure. The results of the study show distinct differences in the national park functions, target groups and their needs. The main target group in KBR is local inhabitants of the million city, and the national park basically fulfils the function of a city park –it is a green area for passive and active (jogging) leisure rather than a nature tourism offer. GNP has three target groups: the local population for a healthy leisure time, domestic visitors and foreign visitors for nature and cultural purposes. Thus, KBR status as a national park is misleading for the international traveller. In the future research it is planned to compare GNP with a national park in India which is located outside the urban environment, carrying out an in-depth study of visitors’ opinion on the purpose and elements of infrastructure.